Metode Psikoedukasi Dan Teknik Shaping Toxic Friendship Bagi Mahasiswa Psikologi Universitas Darul Ulum - Resky Sylvia Santoso; D. Annisah Dwi Farhani; Windy Widyaningrum; Dika Aulia Almaghfiroh; Basyid Firnanda (Jurnal Pengabdian Masyarakat Universitas Darul Ulum, 2024)
Abstract Psychoeducational methods and shaping techniques through socialization activities aim to increase students' understanding of what aspects are related to Toxic Friendship. This socialization is part of the activities for community service for psychology students class 2020 at Darul 'Ulum University which is carried out by applying psychoeducational methods and shaping techniques through socialization activities regarding Toxic Friendship, giving short questions about Toxic Friendship, and providing Toxic Friendship modules for students. The final results of this community service show that there is an increase in students' understanding of what aspects related to Toxic Friendship are known through the increase in the number of students who are able to answer correctly the short questions given before and after the socialization is carried out.